2020
DOI: 10.25259/jgoh_22_2020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of statins as local drug delivery agents in treating chronic periodontitis and their antimicrobial effects using polymerase chain reaction

Abstract: Objectives: The aim of the study was to evaluate the anti-inflammatory effect of statin medication in chronic periodontitis patients and to compare the change in periodontal probing depth and clinical attachment level using 1.2% atorvastatin (ATV) gel and scaling and root planning (SRP) compared to SRP alone. Materials and Methods: This study was carried out on a sample size of 40 patients with equal male and female ratio between the age group of 40–60 years having chronic periodontitis with a minimum of 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Furthermore, it has been demonstrated that the local administration of statins (in particular, ATV and RSV) in adjunct to SRP may result in additional significant improvement in terms of CAL gain and PPD reduction compared with SRP alone [ 21 ]. Also, Singh et al [ 22 ] revealed that stains are effective in improving periodontal parameters along with anti-inflammatory, osteoconductive, and antimicrobial effects.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that the local administration of statins (in particular, ATV and RSV) in adjunct to SRP may result in additional significant improvement in terms of CAL gain and PPD reduction compared with SRP alone [ 21 ]. Also, Singh et al [ 22 ] revealed that stains are effective in improving periodontal parameters along with anti-inflammatory, osteoconductive, and antimicrobial effects.…”
Section: Discussionmentioning
confidence: 99%